The Smart chicken coop: Automated lighting with Google Home - Nurfarida, Ellya; Izzah, Abidatul; Bakhtiar, Yohan; Riskitasari, Septyana; Aullia, Fikha Rizky; Habibi, Isac Ilham (Universitas Muhammadiyah Magelang, 2025)
Nur Kholiq Chicken Farm is a traditional chicken farm with a significant turnover in Blitar Regency that still relies on an inefficient conventional lighting system. Addressing this issue, this community service aims to implement an automatic lighting control system in the chicken coop using Google Home, smart lamps, and internet connection, enabling remote control via smartphone. This community service's activities included discussions with partners, procurement of equipment, system installation, user training, and evaluation. The evaluation demonstrated the successful implementation of the Google Home and smart lamp-based automatic lighting control system at Nur Kholiq Chicken Farm, as well as a significant increase in the partner's knowledge regarding the use of this technology.